Predictors of cardiac implantable electronic device infection in the United States. (14th October 2021) - Shah, K; Modi, V; Gandhi, H; Thyagaturu, H; Walker, A; Shirani, J
Abstract: Background: Cardiac implantable electronic devices (CIED) are important tools for managing arrhythmias, improving hemodynamics, and preventing sudden cardiac death. Device infection (DI) remains a significant complication of CIED and is associated with high morbidity, mortality, and healthcare cost. Purpose: To analyze predictors of DI and its in-hospital outcomes. Methods: National Inpatient Sample 2011–2018 database was analyzed for admissions for CIED implantation or DI. Baseline and hospital level characteristics were derived. The Chi-square test and student t-test were used for comparison of categorical and continuous variables respectively. Variables with p<0.20 from univariate analysis were included in the multivariate logistic regression to identify independent predictors of DI. Results: A total of 1, 604, 173 admissions for CIED implantations and 71, 007 (4.4%) admissions for DI were reported during 2011–2018. There was no significant change in annual admissions for DI (range 8550 to 9307, p for trend=0.98). Those with DI were more likely to be male (69.3 vs 57%, p<0.001) and had higher Charlson comorbidity index score ≥3 (46.6%-vs-36.8%, p<0.001). Multivariate analysis identified post-procedural hematoma (odds ratio (OR)=3.96; 95% Confidence Interval (CI)=3.46–4.54), congestive heart failure (CHF; OR=2.80, 95% CI=2.66–2.96), age group 45–60 years (OR=2.46, 95% CI=2.30–2.63), malnutrition (OR=1.99, 95% CI=1.85–2.15), coagulopathy (OR=1.75, 95% CI=1.64–1.86), end-stage renal disease (OR=1.65, 95% CI=1.53–1.78), atrial fibrillation (OR=1.42; 95% CI=1.35–1.49), non-Hispanic race (OR=1.25; 95% CI=1.16–1.36), coronary artery disease (OR=1.21; 95% CI=1.15–1.26), and thyroid disease (OR=1.15; 95% CI=1.09–1.12) [all p<0.001] as independent predictors of DI. Prevalence of CHF, malnutrition, and atrial fibrillation increased in those admitted with DI over the observation period as shown in Figure 1 (p for trend <0.001). Prevalence of diabetes mellitus also increased during the observation period although it was not an independent predictor of DI (p for trend <0.001). Pulmonary embolism and deep vein thrombosis were most common complications in those with DI (4.1 and 3.6% respectively). Annual in-hospital mortality ranged from 3.9 to 5.7% (mean 4.4%, p for trend=0.07). Conclusion: DI is relatively common and continues to be associated with high morbidity and mortality. Prevalence of DI has not changed significantly despite technical and technological advances in device implantation. Evaluation of risk factors for DI and management of modifiable comorbidities may be needed to reduce the incidence of this important complication of CIED implantation. Funding Acknowledgement: Type of funding sources: None.